تقييم نقدي للأطر النظرية والتطبيقات الراهنة لتقنيات الواقع الافتراضي والمعزز في التدريب المهني (Comprehensive Journal of Science, 2025)
This theoretical study aims to provide a critical and integrative evaluation of the theoretical frameworks and contemporary applications of Virtual Reality (VR) and Augmented Reality (AR) technologies in professional training, in response to the transformations imposed by the Fourth Industrial Revolution. The study adopts a descriptive-analytical approach through a Systematic Literature Review (SLR) of peer-reviewed academic publications published between 2018 and 2025, focusing on the impact of immersive technologies on skill acquisition, knowledge retention, and skill transfer to real-world work environments.The findings indicate that the effectiveness of VR and AR technologies is highly dependent on the training context and the type of targeted skills. Virtual Reality proves to be more effective in training complex procedural skills and high-risk simulations, while Augmented Reality significantly contributes to reducing errors and managing cognitive load during real-time task performance. The study also reveals that inconsistencies in previous research findings stem from variations in theoretical frameworks and levels of functional fidelity adopted in immersive environment design.Based on these findings, the study proposes an integrative theoretical framework, the Interactive Factor-Learning Model (IF-L Model), which highlights the mediating role of functional fidelity, controlled sensory interaction, and technological motivation in shaping learning outcomes. The study recommends adopting a hybrid training approach that strategically integrates VR and AR technologies, alongside establishing clear ethical and regulatory frameworks for immersive data governance, to ensure effective and sustainable implementation of immersive technologies in professional training.
Keywords: Virtual Reality, Augmented Reality, Professional Training, Immersive Learning, Skill Transfer, Cognitive Load.